Intestinal and pancreas enzyme activity of broilers exposed to thermal stress - Routman, KS [UNESP]; Yoshida, L [UNESP]; Frizzas de Lima, AC [UNESP]; Macari, Marcos [UNESP]; Pizauro Jr., JM [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2003)
Thirty-two Hubbard broilers were raised under commercial husbandry to evaluate the effect of temperature exposure (26 and 35ºC) on the activity of digestive enzymes at different ages (23 and 46 days) and different diet energy levels (2,900 and 3,200 kcal ME/kg). Data were analyzed in a 2x2x2 factorial arrangement (energy/temperature/age) in a completely randomized design. Animals were slaughtered after four hours of heat exposure for sampling of an intestinal segment, to extract alkaline phosphatase, and pancreas, to extract amylase, lipase and trypsin. The activity of intestinal alkaline phosphatase was influenced by energy level and animal age. Energy level of diet and environmental temperature interfered on the activity of pancreatic amylase. Lipase activity was affected only by broiler age. There was no effect of treatments on pancreatic trypsin activity. It was concluded that the activity of the pancreatic enzymes can be regulated by different mechanisms under stress conditions induced by heat.
Keywords: Broilers; Digestive enzyme; thermal stress